2012
DOI: 10.4103/0972-124x.100922
|View full text |Cite
|
Sign up to set email alerts
|

Dental health education through the brushing ROBOTUTOR: A new learning experience

Abstract: Aim:In the present study, a new electronic model ROBOTUTOR was designed to compare the efficacy of different modes of dental health education for demonstration of the Bass toothbrushing technique and also to evaluate its efficacy with different modes of dental health education in patient understanding.Materials and Methods:Total 150 subjects were randomized into two groups, Group 1 (Questionnaire) and Group II (Investigators). Subjects with history of gingivitis and only mild periodontitis were included. Demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…6 Ahire et al described a technique in which a robot (ROBOTUTOR) was used to demonstrate Bass toothbrushing technique to adults and concluded that it can save clinician’s chair side time as well as help in effective demonstration of the brushing technique. 7 The present study is the first to put forth the oral health intervention concept and also the reinforcement of messages on oral health through the play-way method.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…6 Ahire et al described a technique in which a robot (ROBOTUTOR) was used to demonstrate Bass toothbrushing technique to adults and concluded that it can save clinician’s chair side time as well as help in effective demonstration of the brushing technique. 7 The present study is the first to put forth the oral health intervention concept and also the reinforcement of messages on oral health through the play-way method.…”
Section: Discussionmentioning
confidence: 92%
“…It can be an alternative for teaching basic health concepts. 5 Various methods like board games, 5 drama, 6 robots 7 have been used for health education purposes. There is limited evidence regarding the effectiveness of games in oral health education and the resultant change in oral hygiene status.…”
Section: Introductionmentioning
confidence: 99%
“…ROBOTUTOR is another dental education robotic system explained in the literature [ 94 ]. This robot was an alternative system to a dentist for showing tooth-cleaning procedures (i.e., tooth brushing) to patients.…”
Section: Robots In Dentistrymentioning
confidence: 99%
“…This robot was an alternative system to a dentist for showing tooth-cleaning procedures (i.e., tooth brushing) to patients. According to a study [ 94 ], the patients reported the ROBOTUTOR as the most attractive technique for dental education than other techniques (i.e., audio-video tutorial or dentist). However, the ROBOTUTOR was found to be less efficient as compared to the dentist [ 94 ].…”
Section: Robots In Dentistrymentioning
confidence: 99%
“…There are three main topic areas within the oral health education including: oral hygiene, proper nutrition and using fluoride compounds. The class topics should be adapted to the age of pupils and varied using models, slides, videos, games, computer programmes, role-playing and other activities (Kwan 2005 ; Ahire et al 2012 ; Geetha Priya et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%